2015
DOI: 10.32468/be.870
|View full text |Cite
|
Sign up to set email alerts
|

Maternity and labor markets : impact of legislation in Colombia

Abstract: Our research seeks to determine the impact on female labor outcomes of the amendment on the Colombian labor law in which maternity leave was extended from 12 to 14 weeks (through Law 1468 of July 2011). To identify this impact we compare labor market outcomes of two groups of women with differences in their fertility rates. We find evidence that as a result of the extension of the maternity leave period, women in the high-fertility age group have experienced an increase in inactivity rates, informality, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
5
1
1
Order By: Relevance
“…This could drive down female employment rates and in turn discourage female labor force participation. Comparing women of childbearing age to women past peak fertility in Colombia before and after enactment of legislation which extended maternity leave by two weeks, Bustamante et al (2015) find that the legislation led to a decrease of 0.7 percentage points in female labor force participation among women of childbearing age who have more than a high school education, and a decrease of 0.9 percentage points for women with less than a high school education10. However, the study also finds that women of childbearing age are more likely to be self-employed or working in the informal sector after the policy change.…”
Section: Worker Protection and Firm Incentivesmentioning
confidence: 98%
“…This could drive down female employment rates and in turn discourage female labor force participation. Comparing women of childbearing age to women past peak fertility in Colombia before and after enactment of legislation which extended maternity leave by two weeks, Bustamante et al (2015) find that the legislation led to a decrease of 0.7 percentage points in female labor force participation among women of childbearing age who have more than a high school education, and a decrease of 0.9 percentage points for women with less than a high school education10. However, the study also finds that women of childbearing age are more likely to be self-employed or working in the informal sector after the policy change.…”
Section: Worker Protection and Firm Incentivesmentioning
confidence: 98%
“…33 This Law was very important for Colombian women. As Ramírez, Tribín and Vargas (2015) pointed out, Colombia was one of the first countries that accepted the International Labor Office (ILO) recommendations (Convention No. 3, 1919) on the labor rights of pregnant women ( Table 7).…”
Section: Graph 30mentioning
confidence: 99%
“…Despite Research for Colombia has shown evidence that women suffer the effect of discrimination in access and permanence in formal employment due to pregnancy and care-work responsibilities (Ramírez-Bustamante, 2019). Women of reproductive age are less likely to be hired in formal employment due to the pregnancy employment protection, which more often leads to unemployment, inactivity, or transition to informality where no contributions are made (Ramírez-Bustamante, Tribín-Uribe and Vargas, 2015). For example, according to the Demography and Health Survey (2015), it is still a common practice to ask prospective candidates in the labor market for a pregnancy test.…”
Section: Labor Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…A esto se suman algunos reveces, que habrían podido tener los cambios recientes en la forma de regular la maternidad. Cada vez que se ha intentado proteger el empleo de las madres o de extender los beneficios de las licencias de maternidad, alguna evidencia indica que se terminan deteriorando las condiciones laborales de las mujeres en edades fértiles cuando se comparan con otras de más edad (Molinos Iragorri, 2012;Ramírez Bustamante, Tribin Uribe y Vargas, 2015).…”
Section: Introductionunclassified